The Effect Of Variation Of Welding Camp On The Strength Of The Arc Joint Welding Sheltered Metal Arc Welding (SMAW) On Steel St 37 - Ahmad Bakhori; Muksin R Harahap; Suhardi Napid (CV. AFDIFAL MAJU BERKAH, 2023)
In this study will discuss the extent to which the strength of the st37 steel or low carbon steel arch test after welding Shielded Metal Arc Welding (SMAW). ST37 steel or low carbon steel is formed into specimens with three models of kampuh, namely Double V kampuh 60°, single V kampuh 60° and single slope kampuh 30° as many as 9 (nine) specimens. Furthermore, welding with a current of 90 A and electrode e 6013 then performed a curved test to determine its mechanical properties through the test Universal Testing Machine (UTM) type Tarno Test UPH 100 kN at the State Polytechnic Laboratory Medan. From the data obtained after the analysis can be concluded that the specimen of Type V double camber has the highest value of curved strength is the value of the average curved strength of 1063.96 MPa, of Type V single and single slope camber. This is possible because there are two sides of welding and a large angle of 60° which makes the Weld strong. While the type of single slope welding camp has the lowest arch strength value due to the small welding angle of 30° which makes the welding process difficult and the electrode is not completely filled at the root of the Weld.